Proceedings of the 5th ACM International Conference on Collaboration Across Boundaries: Culture, Distance &Amp; Technology 2014
DOI: 10.1145/2631488.2631498
|View full text |Cite
|
Sign up to set email alerts
|

Come_in@palestine

Abstract: Come_IN computer clubs are a well-established approach to foster learning, social networks and integration in German neighborhoods with a high percentage of migrant population. We have transferred this concept to a different part of the world: a Palestinian refugee camp. Similar to the German neighborhoods we deal with, refugee camps are also the result of migration moves; however, in this casean enforced one. This paper describes the come_IN approach and investigates its adaptation to a Palestinian refugee ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 16 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…Taking experience from the West and adapting it to development contexts should not be implemented without taking some precautions [1,29]. Our study can provide practical insights for other researchers, system designers, and local stakeholders addressing similar challenges.…”
Section: Design Implicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taking experience from the West and adapting it to development contexts should not be implemented without taking some precautions [1,29]. Our study can provide practical insights for other researchers, system designers, and local stakeholders addressing similar challenges.…”
Section: Design Implicationsmentioning
confidence: 99%
“…e e orts are relatively decentralized re ecting their diverse and unique situations. For example, Aal et al migrated computer clubs from their experience with migrants in Germany to refugees in Palestine to foster learning, social networks and integration with local environment [1]. Using qualitative eld notes and interview data, they found that refugees were eager to engage in projects, especially those involving technologies, despite the constant hurdles posed by poor or inconsistent access to the Internet and electricity.…”
Section: Ictd With Refugeesmentioning
confidence: 99%
See 2 more Smart Citations
“…Research that seriously engages with long(er) term design processes from diverse perspectives and theoretical orientations is sorely needed. Early efforts of this ilk in the human-computer interaction (HCI) community can be found around domains such as conflict and post-conflict situations (Aal et al, 2014;Durrant et al, 2014;Mark and Semaan, 2009;Smyth et al, 2010;Wallace et al, 2014), crisis informatics (Burns and Eltham, 2009;Starbird and Palen, 2012), collapse informatics (Tomlinson et al, 2013), cultural heritage (Liu, 2010) and sustainability (Bidwell et al, 2013;Blevis, 2007). The work reported here joins this literature-in the context of recovering from genocide and the development of systems of transitional justice-and draws from the theoretical framing of multilifespan design .…”
Section: Introductionmentioning
confidence: 99%